Significance and Symbolism of Marian Crowns in Post-Tridentine Paintings (1550–1800) - Staněk, Karel (Religion and the arts, 2024)
Marian art in the post-Tridentine period has already been studied from a number of angles but Marian crowns have so far received little attention. They appeared not only in coronation scenes of the Virgin Mary but also in a whole range of other Marian scenes. The crowns given to the Virgin Mary indicate seriousness and authority. She appeared as the majestic Queen of Heaven. The Roman Catholic Church and monarchs used it to legitimize their power. The crowns took on different forms—they used to be depicted mostly as made of precious metals, less often as flower wreaths or circles of stars. Although they were mostly a product of artistic imagination, I argue that the crowns used to be a reflection of actual royal crowns for the purpose of legitimizing royal power. I present several examples from countries whose rulers have declared the Virgin Mary as their patroness and protector.